PENGARUH LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA KARYAWAN MELALUI MOTIVASI KERJA PADA PT. FUBORU INDONESIA - Novia Milenia Putri (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aims to analyze and examine the effect of the non-physical work environment on job satisfaction through work motivation. The type of research is explanatory research using a quantitative approach. The number of samples is 53 employees of the manufacturing company. The data is collected using a questionnaire. The measurement scale used in this study is a Likert scale—data analysis technique using Structural Equation Modeling (SEM) and processed using SmartPLS 3.0 software. This study indicates: that there is a positive and significant influence between the non-physical work environment on employee job satisfaction; there is a positive and significant influence between the non-physical work environment on work motivation; there is a positive and significant influence between work motivation on employee job satisfaction. This research has implications for manufacturing companies, especially regarding the non-physical work environment, motivation, and employee job satisfaction. Companies must maintain and improve the non-physical work environment and work motivation in the company, thereby creating and influencing the increase in employee job satisfaction.